Whoever wants better healthcare simply pays more: citizens' perception about voluntary private health insurance in Colombia - Daniel Felipe Patiño-Lugo; Claudia Marcela Vélez; Diana Patricia Díaz-Hernández; Olga Francisca Salazar-Blanco; Juan Esteban González-Arango; Juan Carlos Velásquez-Correa; Leydi Camila Rodríguez-Corredor; Viviana María Vélez-Marín; Pamela Velásquez-Salazar (BMC, 2024)
Abstract Objectives To explore the perceptions that Colombians have about voluntary private health insurance plans (VPHI) in the health system to identify the tensions that exist between the public and private systems. Methods A qualitative case study approach with 46 semi structured interviews of patients, healthcare workers, healthcare administrators, decision-makers, and citizens. Interviews were recorded, transcribed, anonymized, digitally stored, and analyzed following grounded theory guidelines. Results We developed a paradigmatic matrix that explores how, in a context mediated by both the commodification of health and social stratification, perceptions about the failures in the public health system related to lack of timely care, extensive administrative procedures, and the search for privileged care led to positioning VPHI as a solution to these failures. The interviewees identified three consequences of using VPHI: first, the worsening of problems of timely access to care in the public system; second, higher costs for citizens translated into double payment for technologies and services to which they are entitled; third, the widening of inequity gaps in access to health services between people with similar needs but different payment capacities. Conclusions These findings can help decision makers to understand citizens´ perceptions about the implications that VPHI may have in worsening equity gaps in the Colombian health system. It also shows, how VPHI is perceived as a double payment for services covered within social security plans and suggests that the perceived lack of timely access to care in the public systems and the fear that citizens have for themselves or their family members when using suboptimal healthcare are important drivers to purchase these private insurances.